5G NR : architecture, technology, implementation, and operation of 3GPP New Radio standards - Ahmadi, Sassan (Academic Press, an imprint of Elsevier, 2019)
5G NR: Architecture, Technology, Implementation, and Operation of 3GPP New Radio Standards is an in-depth, systematic, technical reference on 3GPP's New Radio standards (Release 15 and beyond), covering the underlying theory, functional descriptions, practical considerations and implementation of the 5G new radio access technology. The book describes the design and operation of individual components and shows how they are integrated into the overall system and operate from a systems perspective. Uniquely, this book gives detailed information on RAN protocol layers, transport, network architecture and services, as well as practical implementation and deployment issues, making it suitable for researchers and engineers who are designing and developing 5G systems. Reflecting on the author's 30 plus years of experience in signal processing, microelectronics and wireless communication system design, this book is ideal for professional engineers, researchers and graduate students working and researching in cellular communication systems and protocols as well as mobile broadband wireless standards. Strong focus on practical considerations, implementation and deployment issues; Takes a top-down approach to explain system operation and functional interconnection; Covers all functional components, features, and interfaces based on clear protocol structure and block diagrams; Describes RF and transceiver design considerations in sub-6 GHz and mm Wave bands; Covers network slicing, SDN/NFV/MEC networks and cloud and virtualized RAN architectures; Comprehensive coverage of NR multi-antenna techniques and beamformed operation; A consistent and integrated coverage reflecting the author's decades of experience in developing 3G, 4G and 5G technologies and writing two successful books in these areas.